Relative efficiency of different sources of sulphur on yield and soil nutrient status in kharif rice (Oryza sativa) - Mishra, Ambika Prasad; Dash, Ashish Kumar; Panda, Narayan; Prusty, Meenakhi; Sahu, Suman G (ORYZA-An International Journal of Rice, 2021)
A field experiment was carried out in order to study the relative efficacy of different sources of sulphur in kharif rice (Cv. Swarna Sub 1) under mid-central table land zone of Odisha. It was carried out in RBD with 10 treatments and 3 replications. Four different sources of sulphur (Single Super Phosphate, Calcium Sulphate, Elemental S0 and Navaratna as (20-20-0-13) were used with two methods of application as basal & top dressing to rice crop during Kharif season. The treatment details consists as T1 = Control (No Sulphur), T2 = Basal application (B.A) of 30 kg S ha-1 through Calcium Sulphate (CaSO4), T3 = Basal application of 30 kg S ha-1 through Elemental S ( ES ) , T4 = Basal application of 30 kg S ha-1 (through SSP) , T5 = Basal application of 30 kg S ha-1 (through 20-20-0-13) , T6 = Twice application of 15 kg S ha-1 as basal and top dressing through CaSO4, T7= Twice application of 15 kg S ha-1 as Basal application & top dressing through ES , T8 = Twice application of 15 kg S ha-1 through SSP each at Basal application & top dressing, T9 = Twice application of 15 kg S ha-1 as Basal application and top dressing through (20-20-0-13) & T10 = Basal application of 30 kg S ha-1 through CaSO4 and SSP @1:1 ratio . Significantly highest pooled mean grain yield (5.41 t ha-1) and straw yield of (5.62 t ha-1) were recorded with T7, whereas the lowest values were recorded with (control) T1 (4.1 t ha-1 & 4.31 t ha-1 respectively). Among different sources of sulphur, the grain yield of rice varied significantly and it followed the trend as Elemental Sulphur (ES) > CaSO4 > SSP > (20-20-0-13). Spilt application of sulphur fertilizer showed a beneficial effect on S uptake and translocation of micronutrients like Fe, Mn, and Zn. The sulphur economic yield efficiency ratio also inversely varied with S applications.